Peracikan Bahan Alam Menjadi Minuman Tradisional (Jamu) untuk Meningkatkan Imun Tubuh dalam Pencegahan COVID-19: Program Pengabdian Masyarakat di Desa Bajuran Bondowoso - Iklil Hasbiallah; Andi Susanto; Samrotul Widad (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program was conducted in response to the COVID-19 pandemic, which significantly affected public health, including rural communities in Bajuran Village, Cermee District, Bondowoso Regency. Since COVID-19 attacks the respiratory system, accessible and affordable preventive efforts are essential. One alternative approach is to enhance body immunity through the consumption of herbal beverages made from traditional Indonesian spices. This program aimed to empower the community in producing and consuming herbal medicine prepared from ginger, temulawak (Java ginger), turmeric, lemongrass, cinnamon, and palm sugar to improve immune function. The implementation stages included obtaining permits, procuring raw materials, preparing herbal drinks using traditional methods, packaging the products, distributing them to residents, and conducting evaluations through documentation and testimonials. The program was carried out over four months, from March to July 2022, targeting the residents of Bajuran Village. The results indicated a positive response from the community. The free distribution of herbal drinks increased public awareness of the importance of maintaining health and strengthening immunity during the pandemic. The program's success was supported by strong teamwork, support from village authorities, and community enthusiasm. Overall, the program successfully encouraged the utilization of local spice-based herbal remedies as an effort to maintain health and improve body immunity.